對虐貓事件的儒家生命倫理學思考——兼論動物權利: Bioethical Reflection on Animal Rights: A Confucian View - WANG, Yungling (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 二O O 六年春，中國發生了一次女子虐貓引發民眾憤怒的事件。許多批評者措詞激烈，不少媒體也介入了對該事件的報道和評論。在這種報道和評論中，包括記者和專家在內，幾乎毫無例外地對女子虐貓的行為給予了否定，他們認為女子虐貓行為殘忍變態，激進者認為虐貓行為侵犯動物權利，中國應當對動物權利保護立法。但是這些認識和評論或者源於生活經驗，或者源於道德直覺，或者源於糢糊不清的道德認知，卻缺乏其正理性的深入的哲學或者倫理學思考，在儒家生命倫理學看來是荒謬的。 對動物權利的主張起源於動物保護運動， 今天的主要代表人物是辛格和湯姆．雷根 (Tom Regan)。但在儒家生命倫理學看來，他們關於動物與人平等和動物享有權利的觀點都是站不住腳的。儒家生命倫理學認為， 萬物之中人為貴， 人的地位無可爭辯地高於動物。儒家思想家幾乎從來沒有把動物放在與人平等的地位上加以考慮， 而是把人放在差等之愛的最高地位。此外，在儒家思想體系中， 動物不但地位低下，而且其心智、認識、行為均不可與人相比。儒家思想家會同意湯姆．雷根關於人是“生活的主體”的觀點，但卻不承認動物也能成為“生活的主體”，理由很簡單，動物沒有父子之親，沒有男女之別，沒有行為規範。儒家經典著作認為，人獸之別，還在於人有禮，而動物則沒有。在儒家看來，道德與倫理只與人類生活有關，而與動物無闕，人與動物的關係不能成為道德之一倫。總之，動物權利無法得到儒家生命倫理學的辯護。 動物權利論危害甚大。抬高動物的權利地位，其實質就是降低人類的權利地位，傷害人類，或者說反人類。主張為動物權利或動物福利立法，是十分危險的事情。 In the spring of 2006, a Chinese woman maltreated a cat and caused indignation in Chinese society. Many individuals launched critiques on the woman with severe tongue, and public media took part in the report and critique of the incident. Some individuals argue that the woman infringed animal rights and the Chinese government should formulate a law to protect animal rights. This essay draws on Confucian moral and intellectual resources to contend that animals do not have rights and the Chinese government should not issue any law on animal rights. The proposition of animal rights came from the modern Western "animal-protecting movement". The primary representative scholars who attempt to argue for animal rights are Peter Singer and Tom Regan: they hold that human beings and animals are equal and animals should have rights. This view, however, cannot fit into Confucian bioethics. On the Confucian view, human beings are the noblest beings in the world. The status of human being is without question higher than the status of animals. Confucian scholars would never give a position to animals that would be same as human beings. Although Confucian scholars can agree with Tom Regan on the view that human beings are "the subjects of life," they cannot accept the view that animals could be "the subjects of life." The Confucian arguments are very clear: Animals do not have the virtue of qin (intimacy) between the father and the son; they do not have the virtue of bie (difference) between the male and the female; and they do not have behavior norms (de). In short, human beings and animals are essentially difference, on Confucianism, because human beings can cultivate the virtues based on the practice of rituals (li, 禮), while animals do not have the practice of rituals at all. Accordingly, from the Confucian perspective, morality or ethics is only related with human life, but is outside of animal life. The relationship between human beings and animals does not belong to the moral relationship. In a word, animal rights cannot be accepted by Confucian bioethics. Upholding animal rights is consequently undesirable. Heightening animal status is equivalent to debasing human status. This is to harm human beings. This paper concludes that legalizing animal rights is very dangerous. DOWNLOAD HISTORY | This article has been downloaded 169 times in Digital Commons before migrating into this platform.